Silica Extraction Based on Quartz Sand Waste Sandblasting PT. Dok Lamongan with Base Method - Theofilia Medya Ratri; Asya Wisma Prastiwi; Mohammad Istnaeny Hudha; Nanik Astuti Rahman (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2024)
Sandblasting is a method used to improve the surface structure of the material by using high pressure. Quartz sand is one of the abrasives used for sandblasting—quartz sand PT. Lamongan DOK contains silica (SiO2) of 83.4%. The method used in this study is the base method. The solvent used is KOH and NaOH with temperature variation of material preparation 600, 900, 1200 oC and variation of extraction time 1, 1½, 2 hours. The results showed that the most optimal variable with NaOH solvent was at the preparation temperature of 900 oC with 2 hours of extraction, and the amount of the extract yield was 28.5%. The following variable is at the preparation temperature of 600 oC with 1.5 hours of extraction, and the amount of the extract yield is 28.3%. Besides that, the optimal variable with KOH solvent is at the preparation temperature of 900 oC with 1.5 hours of extraction, and the amount of the extract Yield is 27.9%. XRD analysis showed that the extract obtained SiO2 in the form of Crystal Cristobalite and Quartz, and the FTIR analysis results detected the presence of O – H alcohol functional groups. It can provide information that sandblasting waste has a reasonably high Silica content, which can be utilized as a product with higher economic value.